Austistic Espectrum Disorder : The History - Herrera-Del Aguila, Dwight Denis (2021)
Many authors have described autism spectrum disorder since the first references made by the German monk Johannes Mathesius were written in the 16th century. Despite the fact that in the 20th century the term "autism" was coined as part of the description of the clinical picture of the patient with schizophrenia, we have seen how over time this concept has evolved to become its own diagnostic entity described in the manuals of psychiatry. This is why this article will focus on reviewing the main authors who contributed to the description of the autism spectrum disorder as well as its evolution in diagnostic manuals.